miR-263b Controls Circadian Behavior and the Structural Plasticity of Pacemaker Neurons by Regulating the LIM-Only Protein Beadex - Xiaoge Nian; Wenfeng Chen; Weiwei Bai; Zhangwu Zhao; Yong Zhang (Cells, 2019)
: Circadian clocks drive rhythmic physiology and behavior to allow adaption to daily environmental changes. In Drosophila, the small ventral lateral neurons (sLNvs) are primary pacemakers that control circadian rhythms. Circadian changes are observed in the dorsal axonal projections of the sLNvs, but their physiological importance and the underlying mechanism are unclear. Here, we identified miR-263b as an important regulator of circadian rhythms and structural plasticity of sLNvs in Drosophila. Depletion of miR-263b (miR-263bKO) in flies dramatically impaired locomotor rhythms under constant darkness. Indeed, miR-263b is required for the structural plasticity of sLNvs. miR-263b regulates circadian rhythms through inhibition of expression of the LIM-only protein Beadex (Bx). Consistently, overexpression of Bx or loss-of-function mutation (BxhdpR26) phenocopied miR-263bKO and miR-263b overexpression in behavior and molecular characteristics. In addition, mutating the miR-263b binding sites in the Bx 3′ UTR using CRISPR/Cas9 recapitulated the circadian phenotypes of miR-263bKO flies. Together, these results establish miR-263b as an important regulator of circadian locomotor behavior and structural plasticity.